Pengaruh Tingkat Literasi Keuangan Terhadap minat Penggunaan Produk Finansial Teknologi Pada Mahasiswa FEBI UIN Sumatera Utara - Mudrikah, Azizah (Rifa'Institute, 2021)
In the BPS survey conducted in February-September 2020, Gen Z reached 75.49 million or 27.94 million out of a total population of 270.2 million, meanwhile, the number of millennials reached 69.9 million (25.87%). With the presence and dominance of the second generation groups who are relatively digitally literate among the regional population, Indonesia hopes to more easily understand these groups as the backbone of digitalization programs for various sectors in the next year. Digital literacy generation. This study aims to determine how big the level of financial literacy in FEBI UIN North Sumatra students and to determine whether or not there is an influence of literacy level on interest in using technology financial products. The research method used is a quantitative method. Data retrieval using a questionnaire distributed via google form with the respondents are students of Islamic Accounting, Management, Islamic Economics, Sharia Insurance and Sharia Banking study programs. Collecting data in this study using a questionnaire method with a Likert scale method and distributed to 100 respondents. In this study, the data analysis technique used was descriptive analysis and simple regression analysis using SPSS 15.0. The results of this study indicate that the literacy rate of FEBI UIN North Sumatra students is known to be 29.10%. It is classified into the Well literate category and there is a positive and significant influence between the level of financial literacy on the interest in using technology financial products